QUALITY OF BERKSHIRE BOAR SEMEN DILUTED WITH A COMBINATION OF BELTSVILLE THAWING SOLUTION AND MELATONIN AT DIFFERENT STORAGE TIMES - Pradnyani, Gusti Ayu Putu Indira; Bebas, Wayan; Pemayun, Tjok Gde Oka; Trilaksana, I Gusti Ngurah Bagus; Laksmi, Desak Nyoman Dewi Indira; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2026)
Berkshire pigs are a popular choice for small and large scale pig farming enterprises worldwide, including in Bali. Berkshire pigs are well known for their superior meat quality and relatively fast growth rate. This study aimed to determine the effect of storage duration on the quality of Berkshire boar spermatozoa diluted with Beltsville Thawing Solution (BTS®) supplemented with melatonin. Semen from Berkshire boars was diluted using BTS® supplemented with melatonin at a concentration of 1.0 mM and stored at a temperature of 15 –20°C. Semen quality was evaluated at different storage intervals: (P1) 48 hours, (P2) 60 hours, and (P3) 72 hours. The observed semen quality parameters included sperm motility, sperm abnormalities, sperm viability, and plasma membrane integrity of spermatozoa, which were examined using smear preparations observed under a microscope. In addition, sperm malondialdehyde (MDA) levels as an indicator of oxidative stress were measured using the Porcine MDA ELISA Kit. Duncan’s multiple range test analysis showed that the storage duration of Berkshire boar semen diluted with BTS® supplemented with melatonin was able to maintain sperm motility, abnormality, viability, plasma membrane integrity, and malondialdehyde levels up to 72 hours of storage, with sperm motility of 40.66%, sperm viability of 53.00%, and sperm abnormalities of 6.33%. These values met the minimum standards set by the Indonesian National Standard (SNI 8034:2023) for liquid boar semen. These results indicate that melatonin acts as an antioxidant capable of neutralizing free radicals, thereby inhibiting the occurrence of oxidative stress in spermatozoa cells.